2016
DOI: 10.1159/000450952
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypersensitivity Reactions to Proton Pump Inhibitors: A Retrospective Experience

Abstract: Background: We previously reported perfect specificity and low sensitivity of skin tests in proton pump inhibitor (PPI)-induced immediate hypersensitivity reactions in a prospective multicenter study. Here, in a retrospective study, we aimed to further evaluate the diagnostic workup procedures and characteristics of the patients with suspected PPI hypersensitivity. Methods: This national multicenter study was conducted as a retrospective chart review of patients with a history of PPI-induced immediate hypersen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…The drug hypersensitivity diagnostic workup could increase sensitivity when determining the causative drug for anaphylaxis [39,40,41,42,43]. However, such information was not recorded in the BPD.…”
Section: Discussionmentioning
confidence: 99%
“…The drug hypersensitivity diagnostic workup could increase sensitivity when determining the causative drug for anaphylaxis [39,40,41,42,43]. However, such information was not recorded in the BPD.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 3 major studies have been published on this subject before: one by Bonadonna et al [19] in 2012 and 2 by Kepil Özdemir et al in 2013 [20] and 2016 [21]. These 3 studies described PPI HSRs confirmed by skin tests or OPTs for 15, 34, and 21 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can cause adverse events (AEs) such as hypersensitivity reactions (HSRs) [2-6]. Some case reports [7-16] and studies [17-21] have shown that cross-reactivity among PPIs does exist. The following 3 main patterns have been identified: reactions to a single PPI, selective cross-reactions, and cross-reactions with all PPIs.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of hypersensitivity reactions to proton pump inhibitors showed lansoprazole to be the most frequently implicated drug, followed by pantoprazole, esomeprazole, rabeprazole, and omeprazole, as well as anaphylaxis being the most frequent manifestation [95]. Since cross-reactions among proton pump inhibitors may occur, alternative drugs should be included in the diagnostic workup [95].…”
Section: Drug Hypersensitivity: the Triad Of Pathomechanism Diagnostmentioning
confidence: 99%
“…A retrospective analysis of hypersensitivity reactions to proton pump inhibitors showed lansoprazole to be the most frequently implicated drug, followed by pantoprazole, esomeprazole, rabeprazole, and omeprazole, as well as anaphylaxis being the most frequent manifestation [95]. Since cross-reactions among proton pump inhibitors may occur, alternative drugs should be included in the diagnostic workup [95]. Rapid desensitization in patients with drug hypersensitivity to biologics, such as rituximab, infliximab, cetuximab, and trastuzumab, for which a detailed protocol has been developed, has been documented as safe and effective [96].…”
Section: Drug Hypersensitivity: the Triad Of Pathomechanism Diagnostmentioning
confidence: 99%